Penyuluhan Bahaya Narkotika, Psikotropika, dan Zat Adiktif di SMPN 1 Sanaman Mantikei - Defilia Anogra Riani; Shesanthi Citrariana; Dea Betriksia (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The abuse of Narcotics, Psychotropics, and Addictive Substances (NAPZA) poses a serious threat to adolescents, including junior high school students. This community service activity aimed to increase students' knowledge and awareness of the dangers of NAPZA through a counseling program conducted at SMPN 1 Sanaman Mantikei. The method involved interactive material presentations, group discussions, and pretest-posttest evaluations. The results showed a significant improvement in students’ knowledge, from 69% to 92% in “good” category after the counseling. This indicates that health education is an effective preventive strategy against substance abuse among adolescents. The activity received positive responses from both students and school staff. Sustainable education programs and integration of NAPZA-related topics into the school curriculum are necessary to build adolescents’ resilience against negative environmental influences. Consistent and collaborative efforts are key to protecting the younger generation from the dangers of drug abuse.